Transient Requirement of the PrrA-PrrB Two-Component System for Early Intracellular Multiplication of Mycobacterium tuberculosis - Ewann, Fanny (American Society for Microbiology, 2002)

(untitled)
Adaptive regulation of gene expression in response to environmental changes is a general property of bacterial pathogens. By screening an ordered transposon mutagenesis library of Mycobacterium tuberculosis, we have identified three mutants containing a transposon in the coding sequence or in the 5′ regions of genes coding for two-component signal transduction systems (trcS, regX3, prrA). The intracellular multiplication capacity of the three mutants was investigated in mouse bone marrow-derived macrophages. Only the prrA mutant showed a defect in intracellular growth during the early phase of infection, and this defect was fully reverted when the mutant was complemented with prrA-prrB wild-type copies. The mutant phenotype was transient, as after 1 week this strain recovered full growth capacity to reach levels similar to that of the wild type at day 9. Moreover, a transient induction of prrA promoter activity was observed during the initial phase of macrophage infection, as shown by a prrA promoter-gfp fusion in M. bovis BCG infecting the mouse macrophages. The concordant transience of the prrA mutant phenotype and prrA promoter activity indicates that the PrrA-PrrB two-component system is involved in the environmental adaptation of M. tuberculosis, specifically in an early phase of the intracellular growth, and that, similar to other facultative intracellular parasites, M. tuberculosis can use genes temporarily required at different stages in the course of macrophage infection.